(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article reflects in this way how important it is for a child to teach a foreign language in preschool educational organizations and how the future generation should be comprehensively mature and learn foreign languages not only knowing their native language. Attention should also be paid to the interests and abilities of learners when teaching a foreign language. At the same time, effective and useful methodologies for teaching the language of English for Foreign Language teachers and parents of educators are also presented.